Labour Skill, Trade Structure and Comparative Advantage of Malaysia's Manufacturing Industries, 1978-1996 - Mohammed, Mohammed Sharif Bashir (2001)
As a small open economy, Malaysia'S development strategy is best formulated with the view of trade-production paradigm. Its development targets should be driven by the condition of demand. A supply-driven approach is not only technically nonfeasible, but also will frustrate development efforts and bring about destabilising effects in the long term. In the context of the recent East Asian crisis, failure to recognise the important force of the external sector has gradually eroded economic fundamentals of the economies. Although a capital-intensive technique of production leads to higher labour productivity, the rate of increase in the physical capital accumulation has to match with that of human capital. In order not to frustrate the external account, skill requirement could be estimated by equalising the skill content for producing trade flows. In this way human capital requirements are integrated into the external account and thus ensure long-term sustainability. An input-output model is used to examine the country's resource allocation in production and trade. Also, an approach of H-O extension has been used to investigate the skill intensity of Malaysian trade by analysing skill content of exports and imports. The results found that Malaysia's comparative advantage lies in low skill while its discomparative advantage relies on the highly skilled.